Migrative Thioamination of Aryne Intermediates Generated from o-Iodoaryl Triflates - Tabata, Shinya; Minoshima, Mai; Kobayashi, Akihiro; Hosoya, Takamitsu; Yoshida, Suguru (Synlett, 2023)
Migrative thioamination of aryne intermediates takes place using various o-iodoaryl triflates and sulfilimines. The selective migration realizes the facile synthesis of a broad range of highly functionalized o-thioaminated diaryl sulfides. We succeeded in the ring expansion of cyclic sulfilimines enabling us to prepare eight- and nine-membered organosulfurs from dibenzothiophene- and thianthrene-type sulfilimines, respectively.
Keywords: arynes; sulfilimines; diaryl sulfides; thioamination; migration